2022
DOI: 10.1093/clinchem/hvac138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Optimal Urinary Biomarkers of Synthetic Cannabinoids BZO-HEXOXIZID, BZO-POXIZID, 5F-BZO-POXIZID, and BZO-CHMOXIZID for Illicit Abuse Monitoring

Abstract: Background The continuous introduction of new synthetic cannabinoid (SC) subtypes and analogues remains a major problem worldwide. Recently, a new “OXIZID” generation of SCs surfaced in seized materials across various countries. Hence, there is an impetus to identify urinary biomarkers of the OXIZIDs to detect their abuse. Methods We adapted our previously reported two-pronged approach to investigate the metabolite profiles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Our study indicated that hydroxylation occurred more frequently at the N-alkyl moiety than at the benzene ring, while the F7 (terminal fluorine atom was oxidized to a hydroxyl group) of 5F-BZO-POXIZID was the most frequently modified group, consistent with some other research results for 5F-AB-PINACA, 5F-MN-18, and MAM-2201 [34,39,54]. We considered that C5-7 and D5-6 represented oxidative dehydrogenation combined with hydroxylation (346.1554 and 332.1392 resulting from hydroxyl dehydration), but H11, H13, P8, and P10 were identified as ketone formations by Lee et al [25], although they only provided one fragment ion. In addition, we did not detect H8 (hydroxylation + ketone) reported by Lee et al [25], although we did identify the metabolites (C24-26) of dihydroxylation combined with dehydrogenation after hydrolysis of BZO-HEXOXIZID.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study indicated that hydroxylation occurred more frequently at the N-alkyl moiety than at the benzene ring, while the F7 (terminal fluorine atom was oxidized to a hydroxyl group) of 5F-BZO-POXIZID was the most frequently modified group, consistent with some other research results for 5F-AB-PINACA, 5F-MN-18, and MAM-2201 [34,39,54]. We considered that C5-7 and D5-6 represented oxidative dehydrogenation combined with hydroxylation (346.1554 and 332.1392 resulting from hydroxyl dehydration), but H11, H13, P8, and P10 were identified as ketone formations by Lee et al [25], although they only provided one fragment ion. In addition, we did not detect H8 (hydroxylation + ketone) reported by Lee et al [25], although we did identify the metabolites (C24-26) of dihydroxylation combined with dehydrogenation after hydrolysis of BZO-HEXOXIZID.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, 12-16 metabolites were previously identified for three OXIZIDs (BZO-HEXOXIZID, BZO-POXIZID, and 5F-BZO-POXIZID) by Lee et al [25]. The major metabolic pathways were consistent with our findings, and the detected compounds included hydroxylated, ketonic, carboxylated, amide-hydroxylated, and N-dealkylated metabolites.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, a combined ester hydrolysis + ketone metabolite was the major urinary metabolite of EDMB-PINACA ( 31 ), and hydroxy + ketone products were some of the most abundant urinary metabolites for adamantyl SCRAs APINACA (AKB-48) and 5F-APINACA (5F-AKB-48) ( 32 ), showing that ketone formation is a major in vivo metabolic pathway for some compounds. Ketone metabolites have also been detected in human liver microsome (HLM) incubations of oxindole hydrazide (OXIZID) SCRAs ( 33 , 34 ), which are significantly different in structure to earlier generations of SCRAs.…”
Section: Resultsmentioning
confidence: 99%